Rollover stability control in steer-by-wire vehicles based on an LPV method. (3rd March 2006) - Gaspar, P.; Szaszi, I.; Bokor, J.
In this paper a combined control structure, which includes an active steering and an active brake system, is proposed for tracking the path of the vehicle. Besides tracking, this control also guarantees the prevention of rollovers. First, a linear parameter varying (LPV) model is constructed, in which both the performance specifications and the model uncertainties are taken into consideration. Then a parameter-dependent LPV controller based on the H∞ method is designed. The control mechanism is demonstrated in various manoeuvre situations.